Central Thalamic Deep-Brain Stimulation Alters Striatal-Thalamic Connectivity in Cognitive Neural Behavior - Lin, Hui-Ching; Pan, Han-Chi; Lin, Sheng-Huang; Lo, Yu-Chun; Shen, Elise Ting-Hsin; Liao, Lun-De; Liao, Pei-Han; Chien, Yi-Wei; Liao, Kuei-Da; Jaw, Fu-Shan; Chu, Kai-Wen; Lai, Hsin-Yi; et al. (Frontiers in Neural Circuits, 2016)
Central thalamic deep brain stimulation (CT-DBS) has been proposed as an experimental therapeutic approach to produce consistent sustained regulation of forebrain arousal for several neurological diseases. We investigated local field potentials (LFPs) induced by CT-DBS from the thalamic central lateral nuclei (CL) and the striatum as potential biomarkers for the enhancement of lever-pressing skill learning. LFPs were simultaneously recorded from multiple sites in the CL, ventral striatum (Vstr), and dorsal striatum (Dstr). LFP oscillation power and functional connectivity were assessed and compared between the CT-DBS and sham control groups. The theta and alpha LFP oscillations were significantly increased in the CL and striatum in the CT-DBS group. Furthermore, interhemispheric coherences between bilateral CL and striatum were increased in the theta band. Additionally, enhancement of c-Fos activity, dopamine D2 receptor (Drd2) and 4-nicotinic acetylcholine receptor (4-nAChR) occurred after CT-DBS treatment in the striatum and hippocampus. CT-DBS strengthened thalamic-striatal functional connectivity, which demonstrates that the inter-regional connectivity enhancement might contribute to synaptic plasticity in the striatum. Altered dopaminergic and cholinergic receptors resulted in modulation of striatal synaptic plasticity’s ability to regulate downstream signaling cascades for higher brain functions of lever-pressing skill learning.